Legal practice in the formative stages of the Chinese empire: an annotated translation of the exemplary Qin criminal cases from the Yuelu Academy Collection - Lau, Ulrich; Staack, Thies (Sinica Leidensia, 2016)
Contents -- Preface -- Chinese Dynasties and Historical Periods (ca. 1000 bc-AD 200) -- Maps of the Qin Empire and the Provinces of the South -- Part 1 -- Introduction -- Chapter 1 part 1: introduction - chapter 1 -- Sources on Early Chinese Law before the Yuelu Academy Finds -- 1.1 Received Literature -- 1.2 Excavated Manuscripts -- Chapter 2 part 1: introduction - chapter 2 -- The Yuelu Academy Manuscript Collection -- 2.1 The Question of Authenticity -- 2.2 Possible Origin of the Collection -- Chapter 3 part 1: introduction - chapter 3 -- The Wei yu deng zhuang Manuscripts